Time Magazine is not for Blockheads:” The American Adam’s Vacillation Between Cultural Homogeneity and Heterogeneity in Edward Albee’s the Zoo Story - Olfa Gandouz (The Journal of Studies in Language, Culture and Society, 2019)
The present paper studies the way media shapes public opinion and aims at creating certain cultural homogeneity in Edward Albee’s Zoo Story (1958). The play is based on a dialogue between two ideologically different characters who do not display the same attitude concerning contemporary culture. Unlike Peter who adheres to cultural conformity, Jerry has a non- conformist attitude as he seeks for subverting contemporary cultural norms. Media is one of the important means that contribute to shape the behavior of Peter and his family. In this context, he reveals that his family has two televisions in the same house and Jerry is implicitly and ironically considering the family as a victim of consumerism. In fact, Jerry’s family is a fine example of the moral and spiritual loss of some American citizens who are easily manipulated and who blindly obey contemporary culture without displaying any critical attitude. In this way, Albee stresses the role of media in serving the capitalist system and in turning the human being into a caged animal. While Albee represents a pessimistic view about the role of cultural conformity in entombing the American Adam and in affecting his faculty of thinking, he offers a glimpse of hope at the final scene. Through the characterization of Jerry, the modern playwright calls for rethinking the role of media and for giving larger space to cultural diversity instead of having a structured way of thinking.